MULTI-STAGE METASOMATISM OF DIAMONDIFEROUS ECLOGITE XENOLITHS FROM THE UDACHNAYA KIMBERLITE PIPE, YAKUTIA, SIBERIA - Misra K.C.; Anand M.; Taylor L.A.; Sobolev N.V. (My University, 2004)
The primary garnet (pyrope-almandine)-omphacite (Cpx 1, 6.5–7wt% Na2O)-sulfide (Fe-Ni-Co mss) assemblage of the two diamondiferous eclogite xenoliths studied (U33/1 and UX/1) experienced two mantle metasomatic events. The metasomatic event I is recorded by the formation of platy phlogopite (~ 10wt% K2O), prior to incorporation of the xenoliths in the kimberlite. The bulk of the metasomatic alteration, consisting of spongy-textured clinopyroxene (Cpx 2A, 1–3wt% Na2O), coarser-grained clinopyroxene (Cpx 2B, 2–5wt% Na2O), pargasitic amphibole (~ 0.8wt% K2O; 3–3.5wt% Na2O), kelyphite (Cpx 3, mostly <1wt% Na2O; and zoned Mg-Fe-Al spinel), sodalite, calcite, K-feldspar, djerfisherite (K5.95Na0.02Fe18.72Ni2.36Co0.01Cu4.08S26Cl ) and a small amount of K-Ca-Fe-Mg glass, is ascribed to the metasomatic event II that occurred also in the upper mantle, but after the xenoliths were incorporated in the kimberlite. A pervasive chloritic alteration (mainly clinochlore + magnetite) that overprints earlier assemblages probably took place in the upper crustal environment. The diamonds are invariably associated with secondary clinopyroxene and chlorite, but the diamonds formed before the entrainment of the xenoliths in the Udachnaya kimberlite.